If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y=4(4y)+44
We move all terms to the left:
y-(4(4y)+44)=0
We get rid of parentheses
y-44y-44=0
We add all the numbers together, and all the variables
-43y-44=0
We move all terms containing y to the left, all other terms to the right
-43y=44
y=44/-43
y=-1+1/43
| y=4(4y) | | 8-2b=-2(=-3;b=0;b=5 | | 3x=5x-8/3 | | 44=2(3x-5 | | 16-15y=-13y-8 | | 3x+7=13(x=-2;x=5) | | -2s-4+13s=13+10s | | -3y+5=50 | | 3+4(2n—1)=6n—2 | | 17-9v=-10v | | 2y+9=-29 | | 54=-9p | | (2x+10)(x-3)=0 | | 8r-8=9-9r | | 18+y=-37 | | n=—0.5 | | 2x=-234 | | 8z=1/8 | | 3t-4=-10+t | | -10(s+3)=-25 | | 3(2x-5=27 | | 3q-4=5q | | x²-2.5x-9=0 | | 8-7h=-3h-9+9 | | -b-6=-2b | | 2(x-3)+4=9-x+7 | | x-2.5-9/x=0 | | -2(2t+2)=-28 | | 6-9(4p-3)=2(6+7)+3 | | |x-5|=|x+2| | | 8+9m=8m | | 8x2−2x−3=0 |